Black "Rantings": Indigenous feminist writers' online narratives in a postfeminist age. - Trott, Verity Anne (AoIR Selected Papers of Internet Research, 2017)
This paper draws on Rosalind Gill's (2007) conceptualisation of the postfeminist sensibility to shape an analysis of how indigenous feminist writers are challenging postfeminist narratives and developing their own counter narratives. A postfeminist sensibility, along with the post-identity ideology that is currently prevalent in Western society, is built upon the narrative that inequalities surrounding gender and race have been conquered and are firmly rooted in the past. To further an understanding of how Indigenous Australian feminist writers are challenging key aspects of postfeminism, this paper examines the ways in which they use the microblogging site Twitter to develop a first-hand and direct engagement with the writers' personal views and to shed insight into how they are challenging postfeminist narratives on an everyday level. With the proliferation of intersectional hashtags created by women of colour, Twitter has been identified as an important tool in the effort to develop "a sustained critique of white feminism" (Daniels, 2016:27; Loza, 2014). While social media sites have been praised for providing alternative and liberating spaces for marginalised feminist voices (Boler & Nitsou, 2014; Halavais & Garrido, 2014; Radsch & Khamis, 2013; Shaw, 2012), there remains a racial disparity between the voices that are elevated online (Nakamura, 2002). This paper asks, how are Indigenous Australian feminist writers challenging aspects of postfeminism online and what are the prevailing counter narratives about women, indigeneity, and feminism?